Chitosan-Lemongrass Essential Oil on Paperboard for Active Food Packaging Applications - Silva, Mariangela de Fátima (2025)
An active film-forming solution of chitosan and lemongrass essential oil was applied as a coating on paperboard, forming an alternative and sustainable packaging material for food applications. The active paper-film systems were characterized by color parameters, thermogravimetric analyses, contact angles, Fourier transform infrared spectroscopy, X-ray diffraction, mechanical properties, and cytotoxicity. The active coated paperboard was homogeneous and yellowish in appearance. The tensile strength (transverse and longitudinal directions) was directly influenced by increasing the number of layers of the chitosan-lemongrass active coating. The oil concentration significantly affected the Taber stiffness (transverse direction). The active coatings with higher concentrations of lemongrass essential oil altered the thermal stability of the coated paperboard. The contact angle values were characteristic of hydrophobic materials. The coated systems presented three characteristic peaks in the X-ray diffraction analysis—2θ = 16.5°, 22.9°, and 29.8°—and an amorphous halo at 18.9°. The cytotoxicity analysis of the active material (1:40:5) indicated potential reductions in the lemongrass essential oil content to maintain cell viability while ensuring insecticidal efficacy, supporting its safe use as food-contact active packaging. In this way, the active packaging system based on a chitosan coating containing lemongrass essential oil on paperboard could be a type of efficient active material packaging which is safe in contact with food and sustainable for the environment.